Visual Depth Perception of 3D CAD Models in Desktop and Immersive Virtual Environments - Girbacia Florin; Beraru Andreea; Talaba Doru; Mogan Gheorghe (INT J COMPUT COMMUN, 2012)
In this paper is presented an experimental study that aims to compare the depth perception of virtual prototypes in immersive virtual environments with the depth perception of CAD models using 2D LCD display. First, a multipurpose solution of a large-scale interactive multi wall projected virtual environment named Holo-CAVE is described and then the conducted experiments are presented. The experiments carried out highlight that perceived depth values estimated for virtual prototypes are signiﬁcantly inﬂuenced by the 3D stereoscopic visualization. Another interesting result of the study is that the estimated depth accuracy increases with the depth size that has to be perceived. The results of experimental study illustrate that the use of immersive stereoscopic visualization is useful during Computer Aided Design related activities.